Curating the Human Experience: Introducing an Inquiry of Literary Texts into Historical Research - Walsh-Moorman, Elizabeth (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2021)
This case study follows the process as four high school students curate literary sources in preparation for historical arguments. Results indicate that the use of literary texts prepared students to build nuanced historical arguments by helping them identify subtexts and divergent perspectives through their research. The underlying ELA skills complemented the literacy demands of historical argumentation.